2013
DOI: 10.4236/ojpsych.2013.33034
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and therapeutic implications of psychiatric comorbidity in high functioning autism/Asperger syndrome: An Italian study

Abstract: The present study describes the occurrence of psychiatric comorbid disorders in a cohort of 86 high functioning autism (HFA)/Asperger syndrome (AS) patients, examined at Child Neurology and Psychiatry Unit of Tor Vergata University. 38 patients out of 86 (44.2%) presented one or more psychiatric comorbidities, such as mood disorders, Attention Deficit/Hyperactivity Disorder (ADHD), Tourette syndrome (TS), anxiety disorders, including obsessive-compulsive disorder (OCD), and psychotic symptoms. We compared our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…The study also employed a very selective clinical sample of pre-adolescents and adolescents with HFA, with the majority not receiving their ASD diagnosis until late childhood or adolescence. Still the other studies which investigated HFA reported much higher co-occurrence rates [25][26][27] .…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The study also employed a very selective clinical sample of pre-adolescents and adolescents with HFA, with the majority not receiving their ASD diagnosis until late childhood or adolescence. Still the other studies which investigated HFA reported much higher co-occurrence rates [25][26][27] .…”
Section: Discussionmentioning
confidence: 90%
“…A recent Italian study also investigated the co-occurrence of psychiatric disorders in 86 children with HFA and AS attending a university clinic. 38 patients out of 86 (44.2%) presented with 1 or more additional psychiatric conditions and 7 (18.4%) were diagnosed with BPAD [25] . Hofvander et al [41] assessed 122 consecutively referred adults with normal-intelligence ASD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ASD and other mental disorders are often simultaneously diagnosed, the DSM-IV [1] and the ICD-10 [2] prohibit the diagnosis of ADHD in individuals with an ASD diagnosis. Previous studies indicated that the prevalence of ADHD among individuals with ASD is estimated to be 28.2% [25], particularly among those with HFA/AS its 44% -65% [26,27]. Giovinazzo et al [27] investigated psychiatric comorbidity in 86 high-functioning ASD and reported that 25 subjects (37.9%) had ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that the prevalence of ADHD among individuals with ASD is estimated to be 28.2% [25], particularly among those with HFA/AS its 44% -65% [26,27]. Giovinazzo et al [27] investigated psychiatric comorbidity in 86 high-functioning ASD and reported that 25 subjects (37.9%) had ADHD. Holtmann et al [8] examined 182 PDD subjects and reported that subjects with a severe attention problem exhibited a significantly higher degree of general psychopathology.…”
Section: Discussionmentioning
confidence: 99%